2021
DOI: 10.1051/0004-6361/202141233
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and origin of C2H in NGC 253 from ALCHEMI

Abstract: Context. Observations of chemical species can provide insights into the physical conditions of the emitting gas however it is important to understand how their abundances and excitation vary within different heating environments. C2H is a molecule typically found in PDR regions of our own Galaxy but there is evidence to suggest it also traces other regions undergoing energetic processing in extragalactic environments. Aims. As part of the ALCHEMI ALMA large program, we map the emission of C2H in the central mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 42 publications
9
37
0
Order By: Relevance
“…The high value of cosmic-ray ionization rate we derived in Section 6.3 is consistent with another work from our team that concluded that ζ > 10 −14 s −1 because C 2 H is somewhat abundant even in extremely high A V regions (Holdship et al 2021). The derived value of the cosmic-ray ionization rate is higher than those usually obtained in our Galaxy.…”
Section: Derived Physical Parameterssupporting
confidence: 92%
“…The high value of cosmic-ray ionization rate we derived in Section 6.3 is consistent with another work from our team that concluded that ζ > 10 −14 s −1 because C 2 H is somewhat abundant even in extremely high A V regions (Holdship et al 2021). The derived value of the cosmic-ray ionization rate is higher than those usually obtained in our Galaxy.…”
Section: Derived Physical Parameterssupporting
confidence: 92%
“…The gas densities are consistent with previous measurements. The range of likely density values for each region overlaps very well with those derived from the ALCHEMI observations of C 2 H (Holdship et al 2021). They also fall well within the range of 1 × 10 5 -1 × 10 6 cm −3 found in other ALCHEMI work (Harada et al 2021) and elsewhere (Leroy et al 2018).…”
Section: The Gmc Propertiessupporting
confidence: 85%
“…Points that do not overlap tend to be low-E U SO transitions, which are underpredicted by the model. This is perhaps a similar effect to that seen in C 2 H emission in the same GMCs (Holdship et al 2021), where low-E U emission was clearly excited by an additional gas component. However, because these deficiencies are small, we consider that the majority of the gas emitting these species is well characterized by our model.…”
Section: Model Spectral Line Intensitiessupporting
confidence: 70%
See 1 more Smart Citation
“…For the non-LTE analysis, we use the radiative transfer code RADEX (van der Tak et al 2007) via the Python package Spec-tralRadex 4 (Holdship et al 2021) using HNCO and SiO molecular data (Niedenhoff et al 1995;Sahnoun et al 2018;Balança et al 2018) from the LAMDA database (Schöier et al 2005). This allows us to account for how the gas density and temperature affect the excitation of the transitions and to fit three parameters of interest: n H2 , T kin , and N as well as the beam filling factor.…”
Section: Non-lte Analysis With Radexmentioning
confidence: 99%